Parrésia and the Business of Publishing Contemporary Nigerian Literature. - Alabi, Aliyu Sakariyau (Eastern African Literary & Cultural Studies)
This article explores the dynamics and tensions between literature and publishing through the lens of a Lagos-based publishing company, Parrésia, that began publishing in 2012, considering the ways in which its outputs have been shaped in particular ways by its position within the Nigerian publishing landscape. In doing so, it asks questions such as: How is the business end of the book balanced with the literary and how does this affect the sustainability of publishing ventures such as Parrésia? How has the digital revolution helped to reinvent the physical book form? How are these interventions foregrounding African voices and identities in a global world? This paper argues that despite the challenges faced by Africa-based publishers — the disconnected value chain in the book industry, strained economies, unfriendly business environment and the dominance of western canonisation of literary works — companies like Parrésia through innovation and sheer determination can still eke out a stake in the competitive and 'not so profitable' literary publishing sector. It highlights in particular Parrésia's responsive publishing strategy that works against challenges faced by the Nigerian publishing industry, and embraces opportunities presented by the Nigerian literary space.